Law Student Professional Development and Formation Bridging Law School, Student, and Employer Goals - Hamilton, Neil W. (Social Sciences, 2022)
Although law schools do an excellent job of helping students to 'think like a lawyer', data show that clients, employers, and the legal system require a greater range of competencies. This book offers actionable steps to legal educators to help develop each student's professional identity.